Copper-assisted Wittig-type olefination of aldehydes with p-toluenesulfonylmethyl isocyanide. Issue 15 (30th June 2022) - Wang, Yi-Chun; Chen, Xinyi; Alvey, Gregory R.; Shatskiy, Andrey; Liu, Jian-Quan; Kärkäs, Markus D.; Wang, Xiang-Shan
Abstract : A copper-assisted Wittig-type olefination of aldehydes and p -toluenesulfonyl isocyanide (TosMIC) is disclosed, providing an operationally simple approach to ( E )-vinyl sulfone with various functional groups under mild reaction conditions. Abstract : The Wittig reaction is a valuable and powerful tool in organic synthesis, providing a convenient route from aldehydes and ketones to alkenes. Herein, a novel copper-assisted Wittig-type olefination of aldehydes with p -toluenesulfonylmethyl isocyanide (TosMIC) is disclosed, providing a direct and operationally simple approach to ( E )-vinyl sulfones under mild conditions, compatible with a multitude of common functional groups. Experimental and computational investigations imply that the reaction proceeds through an intriguing electronically-controlled (3 + 2)/retro-(3 + 2) cycloaddition pathway.